2010
DOI: 10.1177/0271121410363831
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Imitation to Young Children With Disabilities: A Review of the Literature

Abstract: Imitation is a primary means through which children learn new skills. Most children learn to imitate without being taught but some children with disabilities fail to develop or use imitation in the absence of direct instruction. The importance of teaching imitation to children with disabilities has been acknowledged, with studies appearing as early as the 1960s. Although recent studies regarding the nature of imitative abilities in children with disabilities have been published, relatively few intervention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
2
36
0
3
Order By: Relevance
“…The literature includes a number of reports that generalization across settings and stimuli is difficult for children with intellectual disabilities, particularly when explicit cues are not provided (e.g., see the review in Ledford & Wolery, 2010). Although limited generalization occurs in most studies, generalization patterns are inconsistent and often quite low, which is consistent with cross modal generalization in the current report.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The literature includes a number of reports that generalization across settings and stimuli is difficult for children with intellectual disabilities, particularly when explicit cues are not provided (e.g., see the review in Ledford & Wolery, 2010). Although limited generalization occurs in most studies, generalization patterns are inconsistent and often quite low, which is consistent with cross modal generalization in the current report.…”
Section: Discussionsupporting
confidence: 78%
“…Although limited generalization occurs in most studies, generalization patterns are inconsistent and often quite low, which is consistent with cross modal generalization in the current report. Also, children with intellectual disabilities may have difficulty in the generalization of non-language tasks such as motor imitation in addition to language behaviors (Ledford & Wolery, 2010), suggesting that generalization is a more global problem extending beyond word learning. That is, difficulty in cross modal generalization in both expressive and receptive modalities is consistent an overall deficit in generalization abilities in children such as those with DS who display intellectual deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Many curriculums designed to help practitioners develop skill programs for children with ASD suggest that imitation training begin with object motor imitation or gross motor imitation (e.g., Maurice et al,1996; Partington, ; Sundberg, ). Ledford and Wolery () also concluded that imitation training should begin with object imitation training. More research is needed to determine if, in fact, it is advantageous to begin imitation training with objects.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step in this line of inquiry, we elected to focus on object imitation because a number of curriculum guides for children with ASD (e.g., Maurice et al,1996; Partington, ; Sundberg, ) and imitation researchers (Ledford & Wolery, ) recommend that object imitation be taught early in the sequence of imitation training. When practitioners teach object imitation to children with ASD, each target action involves the use of an object, usually a toy.…”
mentioning
confidence: 99%
“…One of the most common methods for teaching imitation skills to children with ASD is discrete trial training (DTT; Ledford & Wolery, 2011). In DTT, a therapist presents the child with an instruction, waits for an appropriate response, and provides reinforcement.…”
mentioning
confidence: 99%